2023
DOI: 10.29333/iji.2023.16241a
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Social Networking Addiction and Academic Performance in Students of University

Abstract: There is no doubt whatsoever that social networks affects our lives both positively and negatively. Social media addiction is one of the negative impacts of social networking and affects students on a global scale. The research seeks to find out whether there is a statistically significant relationship between the patterns of social addiction and the academic performance by gender of students at the university. The study used the descriptive approach, through a random sample of 383 students from Al Ain Univers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Ghufron et al [ 70 ] concluded that smartphone-addicted students have lower psychological well-being. Alhrahsheh and Almajali [ 71 ] also found a negative relationship between social network addiction and students’ academic performance in their study.…”
Section: Discussionmentioning
confidence: 75%
“…Ghufron et al [ 70 ] concluded that smartphone-addicted students have lower psychological well-being. Alhrahsheh and Almajali [ 71 ] also found a negative relationship between social network addiction and students’ academic performance in their study.…”
Section: Discussionmentioning
confidence: 75%
“…Table (6) shows that there is a relationship between addiction to the Internet and awareness of its psychosocial effects. The results of Table (7), showed that the level of I.A. is affected by the individual's degree of awareness of the psychosocial effects caused by his addiction.…”
Section: Discussionmentioning
confidence: 99%
“…It has been described as an excessive preoccupation with desires or behaviors related to smartphone use, as well as Internet access or its mismanagement, which causes impairment or suffering. Internet addiction disorder has received significant attention in the media as well as among scientists, and this focus is consistent with advances in technology and access to the Internet (6,7) .…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation